Chlamydia trachomatis Mimicking COVID-19 Chronic Follicular Conjunctivitis - Sukhmandeep Kaur; Zachary Raphael Teibel; Nada Farhat; Adam Atoot; Brett Bielory (Case Reports in Ophthalmological Medicine)
Purpose. To characterize the clinical presentation and report lab findings of Chlamydia trachomatis follicular conjunctivitis in two patients with a positive history of active COVID-19 infection. Participants. Two patients with follicular conjunctivitis with a recent history of COVID-19 infection. Design. Retrospective, noncomparative, case report. Methods. Demographic data including age, gender, and place of residence were recorded. A full exam with an emphasis on inflammatory characteristics and systematic workup. Sample follicles were surgically excised in selected cases, and molecular and histopathological analyses were performed. Results. Both patients were initially treated for viral conjunctivitis. After symptoms failed to resolve, biopsy results indicated that both patients were positive for chlamydia conjunctivitis and treated accordingly. Conclusions. These cases illustrate the role of biopsy as an investigative tool in chronic conjunctivitis and the importance of having a broad differential when treating patients with acute conjunctivitis.